High speed rail and tourism: Empirical evidence from Spain's provinces and cities - Daniel Albalate (European Regional Science Association (ERSA), 2015)
This paper evaluates how changes in the provision of HSR services do affect Tourism outcomes in Spain, a touristic country that has the longest and newest HSR network in Europe. The empirical strategy is based on Differences in Differences panel data methods with double fixed effects. Main data is drawn from the Spanish National Statistical Institute (INE) and covers 50 provinces within a time span of 15 years (1998-2013). For municipalities we consider a sample of touristic cities (identified by the Spanish National Statistical Institute) and we follow their touristic outcomes with monthly data between 2005 comparing the before and after situation. Our preliminary results indicate that High speed rail accessibility does not promote tourist activity, but offers a negative statistically significant impact on tourism outcomes when evaluated at Province level. Timing effects analysis shows that HSR only provides higher numbers of tourists during the first year, but this is reversed soon in the second and third year of operation. This result could be explained by the rigid network design not attached to ridership needs that exerts a substitution effect on air transportation, the main mode for long distance tourist mobility. Finally, the analysis of HSR impacts on touristic cities receiving this mode of transportation does not show any distinguishable change after the inauguration of HSR services.
Keywords: H54; L83; O18; R41; 330; High-speed Rail; Tourism; Transportation